Transmission electron microscopy study of rf-sputtered (Bi, Pb)(2)Sr2Ca2Cu3Oy thin films on MgO substrates - Guldeste, A; OConnor, J; Eastell, C; Grovenor, C; Goringe, M (1997)
The interface of epitaxial c-axis-oriented (Bi, Pb)2Sr2Can-1 CunO2n+4+x thin films grown by rf sputtering on MgO substrates has been investigated by high-resolution transmission electron microscopy. It was found that, in spite of the roughness of the substrate surface, the lattice of the film oriented so that its (002) planes are parallel to the interface. No impurity phase was detected at the interface. Near the substrate the presence of the 2201 phase was observed, with some 2212 phase farther from the substrate, whilst the bulk of the film is 2223 phase with some intergrowth of 2212 phase. From selected-area electron diffraction patterns taken at the interface, it was observed that the large lattice mismatch between the film and MgO substrate did not prevent excellent alignment. © 1997 Taylor and Francis Ltd.